Addressing Patients' Priorities as a Strategy to Improve Value. (14th October 2016) - Wong, Yu‐Ning; Roach, Nancy; Meropol, Neal J.
Abstract : The individual patient perspective is critical to inform assessments of value that drive treatment decisions. There are many elements that patients and providers must weigh, and novel decision support tools are needed to help patients clarify their preferences and goals for treatment and, ultimately, assess the value of therapeutic options.